Percutaneous closure versus surgical ostium secundum atrial septal defect: An integrative review - Felici, Rodrigo Moroni (2022)
Atrial septal defect (ASD) represents about 5% to 10% of all diagnosed congenital heart diseases, it is more common in women, with a prevalence of 1.5 to 3.5 women for each man. Changes in the interatrial septum in the oval fossa are called ostium secundum interatrial communication, which correspond to 75% of all ASD cases. Half of the defects are resolved spontaneously while the other half requires surgical of percutaneous intervention. Although the surgical approach has been used for many years, the development of percutaneous techniques has allowed the transcatheter closure of the ASD ostium secundum with excellent results in short and long terms. However, the wide anatomical variation of ASD can compromise the results of percutaneous treatment. Therefore, an integrative review was carried out in order to compare the surgical and percutaneous closure of ASD ostium secundum pointing out the benefits and complications of both techniques. The results showed that as for effectiveness, safety and mortality, both techniques are equally comparable but the complication rates and reduced hospitalization of percutaneous treatment justifies its indication as the method of choice for the treatment of ASD ostium secundum.